Rice Functional and Genomic Breeding (RFGB) v2.0 database to link genotypic and phenotypic datasets, facilitates access and uploading of genomic data - CGIAR Research Program on Rice (2019)
The newly updated database is already available online and ready to be used by the scientific community.